A Sensor (Optode) Based on Cellulose Triacetate Membrane for Fe(III) Detection in Water Samples - Zulhan Arif; Sri Sugiarti; Eti Rohaeti; Irmanida Batubara (Chemistry, 2023)
Iron is a heavy metal that often contaminates water. High iron concentrations are toxic to human health, so monitoring its presence in water is necessary. Iron in water can be detected using an optical sensor (optode). This research aims to fabricate an optode based on a cellulose triacetate membrane with a selective reagent against Fe(III). The optode was fabricated by mixing cellulose triacetate polymer, a plasticiser (a mixture of oleic acid and acetophenone), aliquot-336, and thiocyanate as a selective reagent. Membrane performance was tested based on working range, linearity, limit of detection and quantitation, precision, and accuracy. The performance of the membrane showed a linear response in the concentration range of 0.1–4 mg/L with a coefficient of determination (R2) of 0.9937, limit of detection of 0.0250 mg/L, limit of quantitation of 0.0757 mg/L, repeatability precision with a relative standard deviation of 3.31%, and an accuracy of 100.49%. Optode selectivity was good for interfering ions Cr(VI) and Pb(II). The colour complex of the optode was stable until the 10th day. The application of iron detection in water samples shows an average concentration of 0.2541 mg/L with good precision and accuracy.